Single-cell analysis of bronchoalveolar cells in inflammatory and fibrotic post-COVID lung disease - Mehta, Puja; Sanz-Magallón Duque de Estrada, Blanca; Denneny, Emma K.; Foster, Kane; Turner, Carolin T.; Mayer, Andreas; Milighetti, Martina; Platé, Manuela; Worlock, Kaylee B.; Yoshida, Masahiro; Brown, Jeremy S.; Nikolić, Marko Z.; et al. (Frontiers in Immunology, 2024)
Background Persistent radiological lung abnormalities are evident in many survivors of acute coronavirus disease 2019 (COVID-19). Consolidation and ground glass opacities are interpreted to indicate subacute inflammation whereas reticulation is thought to reflect fibrosis. We sought to identify differences at molecular and cellular level, in the local immunopathology of post-COVID inflammation and fibrosis. Methods We compared single-cell transcriptomic profiles and T cell receptor (TCR) repertoires of bronchoalveolar cells obtained from convalescent individuals with each radiological pattern, targeting lung segments affected by the predominant abnormality. Results CD4 central memory T cells and CD8 effector memory T cells were significantly more abundant in those with inflammatory radiology. Clustering of similar TCRs from multiple donors was a striking feature of both phenotypes, consistent with tissue localised antigen-specific immune responses. There was no enrichment for known SARS-CoV-2-reactive TCRs, raising the possibility of T cell-mediated immunopathology driven by failure in immune self-tolerance. Conclusions Post-COVID radiological inflammation and fibrosis show evidence of shared antigen-specific T cell responses, suggesting a role for therapies targeting T cells in limiting post-COVID lung damage.